Las Instrucciones de Manuel Riesco a su hijo Miguel: emigración, redes y aprendizaje entre Chile y España a principios del siglo XIX - José Saldaña Fernández; Jaime J. Lacueva Muñoz (Les Cahiers ALHIM)
The present article analyses migratory trends between Chile and Spain in the early 19th century, based on the figure of Miguel Riesco and the Instrucciones given by his father Manuel in 1805. These trends are examined in terms of family and commercial strategies and long-range networks, as well as in terms of the transmission of social and ethical values associated to professional practice. From this perspective, the study of the Instrucciones is organised around four main axes: the first two are related to more concrete and tangible aspects, such as routes, goods, commercial profiles, the agents and their links; the final two deal with more intangible aspects, such as moral and social recommendations, private religious practice, ethical values and the transmission of professional knowledge. In short, the analysis ranges from the most intimate and private realm to the sphere of public and social characterisation; this has allowed, not only for the general outline of the commercial company of the Riesco to be revealed, but for the main tenets of Atlantic commerce during the final years of the colonial period to be defined.